2015
DOI: 10.1093/mnras/stv812
|View full text |Cite
|
Sign up to set email alerts
|

Basic properties of Fermi blazars and the ‘blazar sequence’

Abstract: By statistically analyzing a large sample which includes blazars of Fermi detection (FBs) and non-Fermi detection (NFBs), we find that there are significant differences between FBs and NFBs for redshift, black hole mass, jet kinetic power from "cavity" power, broad-line luminosity, and ratio of core luminosity to absolute V-band magnitude (R v ), but not for ratio of radio core to extended flux (R c ) and Eddington ratio. Compared with NFBs, FBs have larger mean jet power, R c and R v while smaller mean redshi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 98 publications
(151 reference statements)
1
12
1
Order By: Relevance
“…There is no significant correlation between L p and M BH (from previous works, see Table 1) either in the total sample or in the two subsamples, while E p shows a significant positive correlation with M BH (see panels 5 and 6 of Figure 4). Our result is different from that of Xiong et al (2015), which suggested that there is no apparent correlation between synchrotron peak frequency and black hole mass in a sample of more than 100 BL Lacs. There are several reasons that might cause such a discrepancy.…”
Section: Correlations For the Total Samplecontrasting
confidence: 99%
“…There is no significant correlation between L p and M BH (from previous works, see Table 1) either in the total sample or in the two subsamples, while E p shows a significant positive correlation with M BH (see panels 5 and 6 of Figure 4). Our result is different from that of Xiong et al (2015), which suggested that there is no apparent correlation between synchrotron peak frequency and black hole mass in a sample of more than 100 BL Lacs. There are several reasons that might cause such a discrepancy.…”
Section: Correlations For the Total Samplecontrasting
confidence: 99%
“…2 in Massaro et al 2009 and Fig. 1 in Xiong et al 2015). If at the same time the degree of polarization depended on the source class (FSRQ or BL Lac), one could expect an implicit dependence of the polarization fraction on the redshift.…”
Section: Polarization Fraction and Redshiftmentioning
confidence: 89%
“…The γ-ray t damping rest values slightly and systematically lie above the optical relation of Burke et al (2021). In addition, we fit our γ-ray results and the optical results together, resulting in the best-fit relation We get the Eddington ratio (the ratio between the accretion disk luminosity and the Eddington luminosity) for 15 out of 23 AGNs from Xiong et al (2015), which are listed in Table 1. Except for Mrk 421, BL Lac, and OJ 287, the remaining 12 sources have an Eddington ratio between 0.01 and 1.…”
Section: Variability Characteristic Timescales In Relativistic Jetsmentioning
confidence: 99%